2023
DOI: 10.1111/jnc.15754
|View full text |Cite
|
Sign up to set email alerts
|

Ceruloplasmin‐deficient mice show changes inPTMprofiles of proteins involved in messengerRNAprocessing and neuronal projections and synaptic processes

Abstract: Ceruloplasmin (Cp) is a multicopper oxidase with ferroxidase properties being of importance to the mobilisation and export of iron from cells and its ability to bind copper. In ageing humans, Cp deficiency is known to result in aceruloplasminemia, which among other is characterised by neurological symptoms. To obtain novel information about the functions of Cp in the central nervous system (CNS) we compared the brain proteome in forebrains from asymptomatic 4‐6‐month‐old Cp‐deficient (B6N(Cg)‐Cptm1b(KOMP)Wtsi/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Besides, CP plays a more prominent role in iron uptake than release ( Mukhopadhyay et al, 2000 ; Mietto et al, 2021 ). Some recent studies stated that the abnormal CP expression occurring in the brain could be attributed to a few neurological diseases ( Klomp and Gitlin, 1996 ; Qian and Ke, 2019 ; Villadsen et al, 2023 ). At present, the existing literature studies have reported that in the iron-deficient and iron-saturated cells, CP, regardless of concentration, promotes the uptake of transferrin-bound iron and ferric citrate by glioma cells ( Attieh et al, 1999 ; Roy et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, CP plays a more prominent role in iron uptake than release ( Mukhopadhyay et al, 2000 ; Mietto et al, 2021 ). Some recent studies stated that the abnormal CP expression occurring in the brain could be attributed to a few neurological diseases ( Klomp and Gitlin, 1996 ; Qian and Ke, 2019 ; Villadsen et al, 2023 ). At present, the existing literature studies have reported that in the iron-deficient and iron-saturated cells, CP, regardless of concentration, promotes the uptake of transferrin-bound iron and ferric citrate by glioma cells ( Attieh et al, 1999 ; Roy et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%